A comparison of the pulsating and steady jets on flow-induced vibrations and thermal behavior of a sprung cylinder inside an isothermal channel. (February 2022) - Farahani, S.D.; Rabiee, A.H.; Zakinia, A.M.; Mosavi, Amir
Abstract: In this paper, the effect of the pulsating jet from channel walls on the thermal and vibrational behavior of the elastically-mounted cylinder is examined. For the sake of comparison, the efficiency of the steady jet in which the injection velocity is constant has also been taken into account. The primary parameters studied are jet distance, pulsating jet velocity, and frequency. The finite volume method is used to solve flow and energy equations. The dynamic mesh approach is also utilized for the cylinder's motion coupling with a flow field. The results of fluid-solid interaction simulations demonstrate that the pulsating jet acts very successfully in reducing cylinder vibrations, so that at U j = 2, The maximum cylinder displacement magnitude is reduced by 91%, 94%, and 94% for slots 1, 2, and 3, respectively. On the other hand, to reduce the cylinder displacement by the steady jet, the injection velocity must be large enough in which the efficiency decreases significantly as the jet distance increases. The primary reason for the vibration reduction in the steady jet is to suppress the vortex shedding behind a circular cylinder. However, as the jet distance increases, the ability of the steady jet to make changes to vortices decreases, and for this reason, no significant difference in the cylinder displacement magnitude is observed for slot 3. In contrast, the main mechanism for reducing vibrations in a pulsating jet is to change the vortex shedding frequency. Consequently, the cylinder comes out the lock-in region, and the displacement magnitude is reduced independently of jet injection from triple slots.